2016
DOI: 10.1016/j.celrep.2016.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Suppresses Gastric Tumorigenesis in Mice

Abstract: Sox2 expression marks gastric stem and progenitor cells, raising important questions regarding the genes regulated by Sox2 and the role of Sox2 itself during stomach homeostasis and disease. By using ChIP-seq analysis, we have found that the majority of Sox2 targets in gastric epithelial cells are tissue specific and related to functions such as endoderm development, Wnt signaling, and gastric cancer. Unexpectedly, we found that Sox2 itself is dispensable for gastric stem cell and epithelial self-renewal, yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 45 publications
(55 reference statements)
6
47
0
Order By: Relevance
“…SOX2 has been implicated in maintaining malignant stemness properties as an oncogene in several types of cancer 1213 , whereas it acts as a tumor suppressor by modulating Wnt-related and intestinal genes in gastric cancer 39 , indicating the context-dependent behavior of SOX2. Although chronic arsenic exposure reprograms human bronchial epithelial cells to CSCs with SOX2 expression 40 , functional role of SOX2 remains unclear in arsenic-induced CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 has been implicated in maintaining malignant stemness properties as an oncogene in several types of cancer 1213 , whereas it acts as a tumor suppressor by modulating Wnt-related and intestinal genes in gastric cancer 39 , indicating the context-dependent behavior of SOX2. Although chronic arsenic exposure reprograms human bronchial epithelial cells to CSCs with SOX2 expression 40 , functional role of SOX2 remains unclear in arsenic-induced CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In support, GC cell lines reveal mutations at codon 1450 of APC that encodes a truncated form of APC that fails to negatively regulate β‐catenin, which causes constitutive activation of Wnt signalling (Sasaki et al , ). Importantly, several reports have demonstrated that conditional deletion or loss‐of‐heterozygosity of wild type Apc is sufficient to drive gastric hyperplasia and subsequent adenoma formation (Tomita et al , ; Radulescu et al ; Powell et al , ; Sarkar et al , ). Collectively, patient genomics and preclinical mouse models highlight the relevance of APC mutations in driving gastric tumourigenesis, which offer an attractive therapeutic target to treat GC patients.…”
Section: Genetic Lesions Of the β‐Catenin Destruction Complexmentioning
confidence: 99%
“…The combined data indicate a tumorigenic role of Sox2 in many cancers. In contrast, Sox2 appears to act as a tumor suppressor gene in gastric tumors driven by canonical Wnt signal activation, pointing to context-dependent activities of Sox2 in regulating cell proliferation and tumorigenesis 19 .…”
Section: Introductionmentioning
confidence: 99%